Toll-like receptor 8 agonist nanoparticles mimic immunomodulating effects of the live BCG vaccine and enhance neonatal innate and adaptive immune responses - Dowling, David J.; Scott, Evan A.; Scheid, Annette; Bergelson, Ilana; Joshi, Sweta; Pietrasanta, Carlo; Brightman, Spencer; Sanchez-Schmitz, Guzman; Van Haren, Simon D.; Ninković, Jana; Kats, Dina; Guiducci, Cristiana; et al. (Journal of allergy and clinical immunology, 2017)
Newborns display distinct immune responses, leaving them vulnerable to infections and impairing immunization. Targeting newborn dendritic cells (DCs), which integrate vaccine signals into adaptive immune responses, might enable development of age-specific vaccine formulations to overcome suboptimal immunization. Small-molecule imidazoquinoline Toll-like receptor (TLR) 8 agonists robustly activate newborn DCs but can result in reactogenicity when delivered in soluble form. We used rational engineering and age- and species-specific modeling to construct and characterize polymer nanocarriers encapsulating a TLR8 agonist, allowing direct intracellular release after selective uptake by DCs. Chemically similar but morphologically distinct nanocarriers comprised of amphiphilic block copolymers were engineered for targeted uptake by murine DCs in vivo, and a range of TLR8 agonist–encapsulating polymersome formulations were then synthesized. Novel 96-well in vitro assays using neonatal human monocyte-derived DCs and humanized TLR8 mouse bone marrow–derived DCs enabled benchmarking of the TLR8 agonist–encapsulating polymersome formulations against conventional adjuvants and licensed vaccines, including live attenuated BCG vaccine. Immunogenicity of the TLR8 agonist adjuvanted antigen 85B (Ag85B)/peptide 25–loaded BCG-mimicking nanoparticle formulation was evaluated in vivo by using humanized TLR8 neonatal mice. Although alum-adjuvanted vaccines induced modest costimulatory molecule expression, limited TH-polarizing cytokine production, and significant cell death, BCG induced a robust adult-like maturation profile of neonatal DCs. Remarkably, TLR8 agonist polymersomes induced not only newborn DC maturation profiles similar to those induced by BCG but also stronger IL-12p70 production. On subcutaneous injection to neonatal mice, the TLR8 agonist–adjuvanted Ag85B peptide 25 formulation was comparable with BCG in inducing Ag85B-specific CD4+ T-cell numbers. TLR8 agonist–encapsulating polymersomes hold substantial potential for early-life immunization against intracellular pathogens. Overall, our study represents a novel approach for rational design of early-life vaccines. [Display omitted]